Implications of Weight and Body Mass Index for Plasma Donation and Health. (14th November 2012) - Jerrard, Genna A.; Liu, Jing; Case, Rosemary C.; Motevalli, Mahnaz; Bolton, Stephen G.; King, Karen E.; Beigel, John; Brooks Jackson, J.
Abstract : This study determined the percentage of potential plasma donors who could donate plasma in the 3 allowable plasma volume limit categories as specified by the Food and Drug Administration (FDA), as well as the association of the body mass index (BMI) of these individuals with age, blood pressure, oral temperature, and pulse. Of 315 plasma donors analyzed, 107 (34.0%) weighed between 110 and 149 lbs (50.0–67.7 kg), 89 (28.2%) weighed between 150 and174 lbs (68.2–79.1 kg), and 119 (37.8%) weighed >175 lbs (79.5 kg), theoretically allowing collection of an additional 101.4 liters (16% more plasma) from both heavier categories based on FDA standards for plasma donor quantities. BMI was positively associated with age, mean arterial pressure (MAP), and pulse (Pearson's r = 0.36, 0.24, and 0.18, resp., P values <0.05), but not with oral temperature. Average BMI for females was higher than for males (+ 1.8, P = 0.01 ), and BMI for African Americans was higher than for White and Asian participants (+ 2.2 and + 5.1, resp., P s <0.05). A significant association was also found in the sex by race interaction with BMI (P = 0.0004 ). Follow-up analyses suggested a significant difference in BMI by sex among African Americans, higher BMI among African American females than Asian and White males, and higher BMI among White females than African American males (P s <0.05).